HARTE DAN TUNGGUAN : REDEFINISI ADAT TUNGGU TUBANG PADA KOMUNITAS SEMENDE MIGRAN - Zainal Arifin (Jurnal Masyarakat dan Budaya, 2020)
Semende community at Muara Sahung, Bengkulu is ethnic group who migrated from Semende origin (Muara Enim) in South Sumatra Province. Semende community in this Muara Sahung coexist with various communities with a strong patrilineal culture value, where inheritance of property prefer men. In contrast to Semende cultural, with tunggu tubang customary, women (especially the eldest daughter) are important public and preferably as a ruler, and guards who utilize the inheritance his parents. As a cultural identity, tunggu tubang in Muara Sahung community still sustained. But the strong cultural intervention from the communities around it, then going on redefinition of tunggu tubang custom. The process of redefinition is done by the conceptualization of inheritance against itself, so that gave rise to the concept of tungguan (usually in the form of a house), and harte (usually in the form of land). The conceptualization of this custom was eventually also carry consequences where mastery against the tungguan more left to the woman (tunggu tubang), while mastery against harte were handed to men (jenang).